Do Genetic Variations in Broilers Modify Metabolic Responses to the New Climatic Situation? - Abdelhak Karim Mouss; Dalila Hammouche; Rahla Meziane; Hacène Ikhlef (Biology and life sciences forum, 2024)
Algeria faces food and nutritional challenges, and breeding meat chickens could represent a tangible solution to the growing demand for animal protein. This activity plays a vital role in the national economy by creating jobs, stimulating growth, and contributing significantly to food security. However, the activity faces many limiting factors, including the thermal stress generated by the new climate. Meat chickens, known for their sensitivity to heat, enhanced by the presence of feathers and the absence of sweat glands, are exposed to life-threatening situations involving the activity’s production and sustainability. Given all these considerations, the presented work looked at the metabolic responses of two strains of meat chickens, Cobb 500 and Arbor Acres, expressed by the evolution of serum levels of thyroid hormones (T3 and T4) and production indicators. The experiment was conducted under thermal stress conditions widely encountered in northern Algeria during the summer. The results revealed that the Cobb 500 strain has better physiological responses than the Arbor Acres strain. This resulted in significant increases in T3 levels (2.21 ± 0.15 vs. 1.75 ± 0.23 ng/mL; p = 0.00026) and T4 levels (17.81 ± 1.62 vs. 13.28 ± 0.99 pg/mL) observed at the age of 50. The same applied in terms of production indicators with significant improvements in living weight (3421.29 ± 126.33 vs. 2944.56 ± 156.76 g/s; p = 0.0097), average daily gain (72.33 ± 6.66 vs. 61.26 ± 5.44 g/s/j; p = 0.0013), consumption index (1.88 ± 0.22 vs. 2.11 ± 0.34; p = 0.017) and mortality rate (6.98 ± 1.01 vs. 9.21 ± 2.97%; p = 2.0050). The results also highlighted the usefulness of using thyroid hormones as stress indicators and being able to take appropriate measures if necessary.